Konseling Kelompok dengan Bibliokonseling untuk Meningkatkan Motivasi Belajar Peserta Didik di SMP Negeri 14 Pontianak - Mustofa, Zaidul; Yuline; Halida (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2024)
This research is based on high learning motivation which is needed to increase the desire to learn in students. At SMP Negeri 14 Pontianak it was found that there were still students who were identified as lacking motivation in studying in class VIII A. This was characterized by students lacking interest in learning, not enthusiastic about participating in learning, lack of desire to do assignments well, students' environmental conditions are less supportive, they do not get appreciation if they get high grades and students do not have aspirations. The aim of this research is to test the effectiveness of group counseling services using bibliocounseling techniques on the level of students learning motivation. This research uses an experimental research method in the form of Pre-Experimental Design with One-Group Pretest and Posttest Design. The sample in the study was taken using a purposive sampling technique from a population of 34 students, namely 5 students who had low learning motivation. Based on calculations, the Pre-test result was 69.6 in the very low category and the Post-test was 101.4 in the high category. Next, the calculated T was obtained using the Paired Sample T-test, namely -10.577 with a Sig value. (2 tailed) 0.00 < 0.05 which means Ha is accepted and H0 is rejected, and with an N-Gain score of 63.05%. So, it can be concluded that group counseling using bibliocounseling techniques is quite effective in increasing the learning motivation of class VIII A students at SMP Negeri 14 Pontianak.